Ecological factors favouring green leafhopper (Nephotettix virescens) population in rice (Oryza sativa) - RAJU, N; RAJENDRAN, R; KAREEM, A ABDUL (The Indian Journal of Agricultural Sciences, 2013)
Peak occurrence of green leafhopper (Nephotettix virescens (Distant)] on rice (Oryza sativa L.) was noted during September and October in 1991-93. The species composition studied revealed that N. virescens dominated over N. nigropictus (Stal.) during all the peak occurrences in the light-trap as well as field collections. Influence of weather factors on green-leafhopper population for the spring, autumn and winter seasons showed positive association with relative humidity and negative with minimum temperature. Multiple regression equation fitted also showed 68, 77 and 63% association for these 3 seasons respectively to the agro-meteorological factors.